An uncommon perineal embryonal rhabdomyosarcoma in adult: A case report. Issue 52 (30th December 2022) - Qu, Sifeng; Li, Weiwei; Yao, Yuan; Huang, Huangwei
Abstract : Rationale: Embryonal rhabdomyosarcoma (ERMS) is a major subtype of rhabdomyosarcoma, mainly affect children. There is seldom report for perineal ERMS in adults, since its rare location and the age. Patient concerns: A 20-year old male adult was admitted due to the perineal mass. Diagnoses: Diagnosis by histopathological examination of the biopsy sample was ERMS. Magnetic resonance imaging showed the tumor was found in the perineal region, with metastasis to pelvic cavity, right testis, lymph nodes and bone. Interventions: The patient received Isophosphamide and Epirubicin for 4 cycles, followed by Irinotecan and Vindesine Sulfate for 2 cycles, then cisplatin, Dacarbazine and Apatinib for 3 cycles. Outcome: The patient showed no response to chemotherapy. Lessons: Perineal ERMS in adults is very rare. There is still no standard therapy for adult ERMS. Personalized therapy might be promising treatment for each individual.